2007
DOI: 10.1007/s10750-007-9224-9
|View full text |Cite
|
Sign up to set email alerts
|

How can we make new ponds biodiverse? A case study monitored over 7 years

Abstract: A new pond complex, designed to enhance aquatic biodiversity, was monitored over a 7-year period. The Pinkhill Meadow site, located in grassland adjacent to the R. Thames, proved unusually rich in terms of its macrophyte, aquatic macroinvertebrate and wetland bird assemblages. In total, the 3.2 ha mosaic of ca. 40 permanent, semi-permanent and seasonal ponds and pools was colonized by approximately 20% of all UK wetland plant and macroinvertebrate species over the 7-year survey period. This included eight inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(68 citation statements)
references
References 23 publications
3
65
0
Order By: Relevance
“…At the end of three years, the author observed that 80% of the original taxa disappeared and new ones were established in the area. Published data suggests that a period ranging from 20 to 36 months is needed for new communities of macroinvertebrates to stabilise in a newly formed lentic system (Solomini et al, 2003;Williams et al, 2008). During research downstream of Flaming George Dam (USA), Vinson (2001) observed small changes in the invertebrate fauna during the first years after damming: large changes were detected five years after damming.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of three years, the author observed that 80% of the original taxa disappeared and new ones were established in the area. Published data suggests that a period ranging from 20 to 36 months is needed for new communities of macroinvertebrates to stabilise in a newly formed lentic system (Solomini et al, 2003;Williams et al, 2008). During research downstream of Flaming George Dam (USA), Vinson (2001) observed small changes in the invertebrate fauna during the first years after damming: large changes were detected five years after damming.…”
Section: Discussionmentioning
confidence: 99%
“…These small water bodies differ greatly in origin and in morphological conditions such as surface area, depth and volume, and natural and anthrophogenically altered ponds experience different precipitation, insolation, water temperature and catchment nutrient inflow. This great variability therefore contributes to forming different habitats and increasing organism species diversity (Wiliams et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they are also efficient indicators of water quality (Ferreira-Peruquetti & De Marco Junior 2002), due to the preference of both larval and adult stages for certain environmental conditions for their establishment (Corbet 1999, Clausnitzer et al 2009). Odonate larvae may also occur in artificial water bodies (e.g., reservoirs), but their diversity in such environments is little studied (Williams et al 2008) Odonates, as other aquatic animal groups, have been threatened by human activities. About 10% of odonate species worldwide are considered "threatened", 35% are classified as "data deficient", and 6% are "endangered" (Clausnitzer et al 2009).…”
Section: Introductionmentioning
confidence: 99%